2008
DOI: 10.1007/s11010-008-9832-3
|View full text |Cite
|
Sign up to set email alerts
|

Energetic metabolism during acute stretch-related atrial fibrillation

Abstract: Background and methods-Perturbations in energetic metabolism and impaired atrial contractility may play an important role in the pathogenesis of atrial fibrillation (AF). Besides, atrial stretch is commonly associated with AF. However, the atrial energetics of stretch-related AF are poorly understood. Here, we measured indicators of energy metabolism during acute-stretch related AF. PCr, adenine nucleotides and derivatives concentrations as well as the activity of the F 0 F 1 -ATPase and Na,K-ATPase were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…One surprising finding from our study was the paradoxical decrease in the expression of GLUT4 protein in the RA during chronic HF (with the lowest content in RAA), which may induce perturbations in energetic production, and thus may play a role in the pathogenesis of atrial fibrillation, the most commonly sustained arrhythmia in adults, in particular for those with chronic HF (9). Indeed, using a canine model of tachycardia-induced HF, profound deficits in atrial bioenergetics characterized by depletion of ATP and creatine kinase were reported and correlated with the duration of induced atrial fibrillation (4), although the role of atrial glucose metabolism was not assessed in this study.…”
Section: Discussionmentioning
confidence: 77%
“…One surprising finding from our study was the paradoxical decrease in the expression of GLUT4 protein in the RA during chronic HF (with the lowest content in RAA), which may induce perturbations in energetic production, and thus may play a role in the pathogenesis of atrial fibrillation, the most commonly sustained arrhythmia in adults, in particular for those with chronic HF (9). Indeed, using a canine model of tachycardia-induced HF, profound deficits in atrial bioenergetics characterized by depletion of ATP and creatine kinase were reported and correlated with the duration of induced atrial fibrillation (4), although the role of atrial glucose metabolism was not assessed in this study.…”
Section: Discussionmentioning
confidence: 77%
“…Dramatic modifications in cardiac energy metabolism during both chronic and short episodes of AF have been noted in previous studies. 8 Several of the…”
Section: Patient Selectionmentioning
confidence: 99%
“…Meanwhile, valvular heart disease often leads to AF through changing gene, mRNA and even ion-channel protein expression. 43, 44 Given that an acute-stretch AF model suggested a specific modification in atrial myocyte energy, 8 we should also consider that valvular heart disease itself may affect the proteomics results.…”
Section: Influence Of Larger La On Metabolismmentioning
confidence: 99%
“…This is important because conditions that predispose to AF-such as aging, hypertension, coronary artery disease, heart failure, or ventricular or atrial dysfunction-can by themselves contribute to mitochondrial dysfunction and must be accounted for when estimating the impact of AF on mitochondrial function (5,11,15,17). Moreover, it is not clear whether reported changes in myocardial energetics and mitochondrial function (1,27,56) are causative or the consequence of AF or associated conditions; nor is it clear whether the OXPHOS impairment reported in some (32) but not all (5a) animal studies also occurs in the human atria (12,37,50). Increasing evidence has accumulated that oxidative stress plays an important role in the pathogenesis of AF (47,17,62) and elevated oxidative stress markers are present in patients with AF (34,41,43,51).…”
mentioning
confidence: 99%